Transforming legacy organizations turn your established business into an innovation champion to win the future - Oestergaard, Kris 1973- (John Wiley & Sons, 2019)
Expert guidance on how to grow innovation and optimize already-successful areas of established organizations Transforming Legacy Organizations provides real-world advice and research-based information on how to grow innovation by employing new technologies, improving processes, and establishing a culture of creativity and forward momentum. Conventional business wisdom views innovation as the biggest advantage startups have over large, established organizations, often referred to as legacy organizations. This belief is false, especially when considering that 70% of all startups fail within 20 months of their first venture round. The truth is innovation initiatives of legacy organizations have far better chances of succeeding. Organizations with superior resources-money, customers, suppliers, data, employees, infrastructure-can overcome challenges from new entrepreneurial ventures: knowing how to leverage their underutilized advantage is key for achieving sustained, long-term innovation success. Author Kris oestergaard has been teaching established organizations around the world for over 15 years. Transforming Legacy Organizations illustrates how to best pursue innovation to create future success. This book helps leaders to: -Incorporate proven strategies and research-based information into your organization's overall innovation initiatives -Use new technologies to improve processes and increase innovation -Learn to capitalize on your organization's existing resources to beat startups at their own game -Transform innovative concepts into specific products, services, and business models -Reinvent your organization to overcome disruptions in the market and challenges from new competitors Transforming Legacy Organizations: Turn your Established Business into an Innovation Champion to Win the Future is a valuable resource for leaders of established companies such as C-Suite executives, senior managers, and heads of business development, innovation, and digital teams.